Nâng cao tính thực tiễn trong giảng dạy môn Giáo dục chính trị cho học sinh, sinh viên Trường Cao đẳng Sơn La hiện nay - Đào, Thị Hợi; Lò, Mai Thoa (Tạp chí Giáo dục, 2025)
Practicality plays a fundamental role in educational activities, especially in Political Education - a subject that has the function of forming worldviews, scientific methodologies, ideological stances and political qualities for learners. Based on this role, Son La College has implemented many measures to improve teaching effectiveness, focusing on applying the principle of unity between theory and practice. The article presents the theoretical basis for practicality in teaching Political Education, surveys the current status of applying practicality in teaching Political Education at Son La College, thereby proposing a number of practical measures such as updating practical materials, innovating teaching methods on the basis of digital technology and developing political and social thinking for students. The research results contribute to orienting the improvement of the quality of teaching Political Education in the context of educational innovation and digital transformation today.